Contagion in Financial Networks: A Threat Index - Gabrielle Demange (Center for Economic Studies and ifo Institute (CESifo), 2015)
Interbank claims are a concern to regulators as they might facilitate the dissemination of defaults and generate spill-over effects. Building on a simple model, this paper introduces a measure of the spill-over effects that a bank generates when it defaults. The measure is based on an explicit criterion, the aggregate debt repayments, and is bank's specific, affected by the bank's characteristics and links to other banks. Such measure can be useful to a regulator to determine in which banks cash should be injected during a default episode or to evaluate the impact of raising capital before the occurrence of default. The approach applies more generally to a system of entities that are linked through financial claims. This is illustrated to evaluate the consolidated foreign claims of 10 EU countries.
Keywords: G01; G21; G28; 330; default; contagion; systemic risk; financial linkages; intervention policy